The association between regular marijuana use and adult mental health outcomes. (1st October 2017) - Guttmannova, Katarina; Kosterman, Rick; White, Helene R.; Bailey, Jennifer A.; Lee, Jungeun Olivia; Epstein, Marina; Jones, Tiffany M.; Hawkins, J. David
Highlights: Abstaining from marijuana predicts fewer symptoms of alcohol use disorder. Abstaining from marijuana predicts fewer symptoms of nicotine dependence. Abstaining from marijuana predicts fewer symptoms of generalized anxiety disorder. Chronic adult marijuana use predicts more symptoms of substance use disorders. Abstract: Objective: The present study is a prospective examination of the relationship between regular marijuana use from adolescence through young adulthood and mental health outcomes at age 33. Methods: Data came from a gender-balanced, ethnically diverse longitudinal panel of 808 participants from Seattle, Washington. Outcomes included symptom counts for six mental health disorders. Regular marijuana use was tracked during adolescence and young adulthood. Regression analyses controlled for demographics and early environment, behaviors, and individual risk factors. Results: Nonusers of marijuana reported fewer symptoms of alcohol use disorder, nicotine dependence, and generalized anxiety disorder than any category of marijuana users. More persistent regular marijuana use in young adulthood was positively related to more symptoms of cannabis use disorder, alcohol use disorder, and nicotine dependence at age 33. Conclusions: Findings highlight the importance of avoiding regular marijuana use, especially chronic use in young adulthood. Comprehensive prevention and intervention efforts focusing on marijuana and other substance use might be particularly important in the context of recent legalization of recreational marijuana use in Washington and other U.S. states.